Macroeconomic regimes, technological shocks and employment dynamics - Tommaso Ferraresi; Andrea Roventini; Willi Semmler (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
In this work, we investigate the interrelations among technology, output and employment in the different states of the U.S. economy (recessions vs. expansions). More precisely, we estimate different threshold vector autoregression (TVAR) models with TFP, hours, and GDP, employing the latter as threshold variable, and we assess the ensuing generalized impulse responses of GDP and hours as to TFP shocks. We find that positive productivity shocks, while spurring GDP growth, display a negative effect on hours worked at least on impact, independently of the state of the economy. In the 1957-2011 period, the effects of productivity shocks on employment are abundantly negative in downturns, but they are not significantly different from zero in good times. However, the impact of TFP shocks in different business cycle regimes depends on the chosen sample: after the mid eighties (1984-2011), productivity shocks increase hours during recessions. Finally, we express and test some conjectures that might have caused the changes in the responses in different time periods.
Keywords: E32; O33; C32; E63; E20; 330; technology shocks; employment; threshold vector autoregression; generalized impulse response functions